Pete's dragon [videorecording (DVD)] - Chaffey, Don, 1917-1990; Reddy, Helen; Dale, Jim; Rooney, Mickey; Buttons, Red, 1919-2006; Winters, Shelley; Miller, Seton I.; Field, S. S. (Walt Disney Studios Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2009)
A 9-year old boy and his pet dragon (invisible to all but him) run away from his foster parents.